2002
DOI: 10.1007/3-540-36181-2_59
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Vision-Based Flying Robots

Abstract: Abstract. We describe a new experimental approach whereby an indoor flying robot evolves the ability to navigate in a textured room using only visual information and neuromorphic control. The architecture of a spiking neural circuit, which is connected to the vision system and to the motors, is genetically encoded and evolved on the physical robot without human intervention. The flying robot consists of a small wireless airship equipped with a linear camera and a set of sensors used to measure its performance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 15 publications
(15 reference statements)
0
21
0
1
Order By: Relevance
“…In [47] an indoor floating robotic blimp equipped with a camera and placed in a small room with bar-code-like markings on the walls was evolved to produce motion and wall avoidance. An essentially aggregate fitness function was used that averaged magnitude of velocity over each trial period.…”
Section: Evolutionary Robotics and Aggregate Fitnessmentioning
confidence: 99%
“…In [47] an indoor floating robotic blimp equipped with a camera and placed in a small room with bar-code-like markings on the walls was evolved to produce motion and wall avoidance. An essentially aggregate fitness function was used that averaged magnitude of velocity over each trial period.…”
Section: Evolutionary Robotics and Aggregate Fitnessmentioning
confidence: 99%
“…The fitness is proportional to the clockwise rotation of the anemometer, which is an estimate of the forward navigation of the blimp. A preliminary set of experiments indicated that artificial evolution generates in about 20 generations spiking controllers that drive the blimp around the room [41]. Robots equipped with evolved controllers did not totally avoid hitting walls since they are not explicitly asked to do so.…”
Section: Stage Iii: Vision-based Blimpmentioning
confidence: 99%
“…Among the various UAVs platforms such as: fixed wing ( Teo et al (2004) and blimp Zufferey et al (2002) stand out the quadricopters. They are aircrafts heavier than air that have the vertical take-off and landing feature (VTOL).…”
Section: Introductionmentioning
confidence: 99%